The efficacy of bacteriophages FO1a and S16 in the reduction of Salmonella on chicken carcasses in a South African poultry processing environment - Wessels, Kirsten (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.